Restauração de imagens em vibro-acustografia - Leite, Talita Perciano Costa (Universidade Federal de São Carlos, 2008)
Vibro-acoustography is an imaging modality that produces a map of the mechanical response of an object to a localized dynamic radiation force produced by an ultrasound field. This technique has been studied and used in clinical applications as to image calcification in breast tissue and arteries. This work aims to apply restoration algorithms to vibro-acoustography images. The point spread function (PSF) of the system is defined in terms of the acoustic emission of a point-target in response to a dynamic radiation stress of ultrasound. This PSF is used to form the image taking into account depth-of-field effects. The main problem found in the vibro-acoustography image formation is the high blur that this PSF causes to the acquired images, mainly in the depth direction (axial axis). To form the degraded image, digital phantoms were used, of breast for instance, simulating tissues with lesion-like inclusions. Moreover, Gaussian noise is added to the blurring model because of the characteristics of the images acquisition by the real vibro-acoustography system. Restoration filters are studied and applied to the images, and their results are compared visually and quantitatively; acceptable results are obtained. Problems found in the implementation of the restoration algorithms for this system are studied and possible solutions are discussed and applied to the final implementations. With the use of the algorithms high quality images were obtained if compared with the degraded versions, fact that justify the use of these methods in this kind of image. Moreover, the algorithms implemented in this work can be applied to imaging problems with similar characteristics.
Keywords: Processamento de imagens; Restauração de imagens; Filtragem de ruido; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO